Nematode Management in Organic Agriculture - Romy Krueger; Robert McSorley (EDIS)
ENY-058, a 9-page illustrated factsheet by Romy Krueger and Robert McSorley, provides information on plant parasitic nematodes causing damage in organic agriculture and introduces methods for their management. Includes references. Published by UF Department of Entomology and Nematology, January 2008. 2011 reprint of January 2008 content.